Perspectives of type 2 diabetes mellitus management in Algeria: a comprehensive expert review - Mohamed Belhadj; Rachid Malek; Houssem Baghous; Mourad Boukheloua; Zakia Arbouche; Nassim Nouri; Mohammed El Amine Amani; Fethia Sersoub; Mohamed Amine Haireche (Frontiers in Clinical Diabetes and Healthcare)
BackgroundThe health and economic impacts of type 2 diabetes mellitus (T2DM) remain substantial, notably in developing countries.ObjectivesTo provide an in-depth assessment of the T2DM situation in Algeria to understand its multifaceted burden and identify priority areas of intervention.MethodsA systematic literature search was conducted on all published articles about T2DM in Algeria over the past 30 years, including original research, reviews, and case series. The extracted data were thoroughly analyzed and synthesized by a committee of diabetes experts.ResultsAlgerian epidemiological data point towards a constant rise of T2DM prevalence, roughly from 8.9% in 2003 to 14.4% in 2016-2017. The mean onset is around 41 years with women experiencing a greater burden at younger age. Low socioeconomic status, limited education, and lack of health insurance exacerbate T2DM risk and health inequities. Lifestyle and metabolic risk factors are prevalent. Despite advancements in glycemic control, prescribing practices lack standardization, with suboptimal use of antidiabetic drugs and absence of novel drugs in the market. Health and economic burdens are dominated by complications, highlighting inadequate primary and tertiary prevention strategies.ConclusionNotwithstanding the increasing burden of T2DM in Algeria, the healthcare strategies and therapeutic outcomes remain suboptimal. This underscores the necessity for a comprehensive strategy including enhanced prevention, access to novel treatments, standardized practices, along with a patient-centered approach.